Small-signal stability analysis for two-mass and three-mass shaft model of wind turbine integrated to thermal power system. (September 2019) - Singh, Vijay P.; Kishor, Nand; Samuel, Paulson; Singh, Navdeep
Abstract: The integration of large wind power into grid affects the power systems dynamics, operation and control. This paper presents the stability analysis of small-signal models of two-mass and three-mass wind turbine interconnected to thermal power system. The use of two-mass/three-mass model is motivated by the need to deal with flexible modes induced due to intermittent varying of wind speed and low speed shaft stiffness. Initially, eigenvalue analysis is performed to investigate the stability of drive train models and also its union model with thermal system. Next, drive train models of wind turbine and its union model are excited by different wind speed profiles. The decomposition of signal into low frequency oscillation (LFO) modes as collection of intrinsic mode functions (IMFs) computed from Hilbert-Huang Transform (HHT) is achieved. The study suggests excitation of LFO modes in drive train models and the same modes in approximate form can be also found in union model with thermal system.